La salute del civis-fidelis nei distinti ordini dello Stato e della Chiesa cattolica. Le aspettative ascetiche della persona nella connotazione del bene salute (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Autonomia confessionale e sovranità dello Stato: la distinzione tra ordini “distinti” – 2. Il principio di laicità e la valorizzazione delle differenze, nell’inderogabile esigenza di salvaguardia dei diritti della persona – 3. Tutela della salute: diritto fondamentale della Costituzione italiana – 4. La dimensione ascetica dell’individuo nella concezione giuridica del bene salute – 5. La salute nell’ordinamento canonico: connotazione di un bene con valore relativo – 6. La realizzazione “responsabile” della salute e la sua intrinseca connessione con la salvezza nella Chiesa – 7. La sana cooperatiotra Stato e Chiesa nella tutela della salute del civis-fidelis – 8. Conclusioni.ABSTRACTHealth of the civis-fidelis in the different systems of the Italian State and the Catholic Church. The spiritual needs of the individual as included in the meaning of health The meaning of "health" in a legal system depends upon its culture and social development, so that time and space influence the way protection is offered. Nowadays the idea of “health” has enlarged. In the past the meaning of health was intended as a mental-physical well-being; it has now gradually developed to a larger meaning, including a complete physical, mental and social well-being and not merely the absence of disease. Along with Italian constitution, Italy has to pursue and protect the health of any individual, not just citizens. Health is also protected by the Church as a precious gift given by God to man and is closely linked with salvation. Man is called to protect the value of this gift in its widest configuration. Therefore the integral protection of health requires to take into account all the dimensions of the individual, both as civis and fidelis. In order to reach this target it is necessary an open dialogue between civil authorities and religious institution; its importance relies on the primacy of the individual and includes the care of his dignity and the respect of his rights, in mutual respect for the autonomy of the two orders, whose relations are to be seen as a single track and a vital bulwark, a vision inspired by the liberal-democratic system.
Keywords: Laicità e pluralismo